Pengembangan LKPD Berbasis Problem Based Learning Melalui Video Interaktif Berbantuan Google Site Untuk Menstimulasi Kemampuan Berpikir Kritis - Nikmatul Munawaroh; Ni'matush Sholikhah (Jurnal Ecogen, 2022)
Abstract : The purpose of this research is to produce economics teaching materials in PBL financial services institution through interactive videos assisted by google site that are valid, pratical, and can stimulate critical thinking skills. The development model used is 4D, which consists of several stages: definition, design, development and deployment, but development is done up to the product development stage. The subjects of the study were students of class X IPS 1 SMA Negeri 16 Surabaya. The validity of this study lies in the materials, questions and media validation results used to determine the feasibility of the product. Instead, research methods of student survey results are used to determine the usefulness of a product and student response results are used to stimulate students ’critical thinking skills. The results showed that the LKPD developed was valid based on materials, questions and media validators, with high results in the “highly efficient” category. And the practicality of the student answer questionnaire, which gave high results in the category of "very practical". On the other hand, the results of student responses showed high values in the “High” category. The developed LKPD is available to stimulate students' critical thinking skills. Keywords : Student Worksheets, problem-based learning, Interactive Videos, Critical Thinking